The Influence of European Standards of Democratic Elections on the Criminal-Legal Protection of The Electoral System of Ukrain - Колодін, Денис Олексійович; Колодін, Д. О.; Kolodin, Denys O.; Чугуніков, Ігор Іванович; Чугуніков, І. І.; Chuhunikov, Ihor I.; Колодіна, Анна Сергіївна; Колодіна, А. С.; Kolodina, Anna S. (Denmark : Faculty of Law Aalborg Academy of Sciences, 2024)
For the democratization of any electoral system, an important role is played by the creation of conditions for the full and free exercise of citizens' electoral rights. At the same time, responding to illegal behavior and bribery of voters during the election process plays a significant role. Given the intensification of election processes in Ukraine, the issues related to the content of the phenomenon of bribery in a criminal offense against the electoral system are particularly relevant and require research. The purpose of the work is to study the phenomenon of bribery in the criminal offense against the electoral system. The research methodology is such methods as dialectical method, dogmatic (formal-logical) method, systemic-structural method, comparative-legal method, formal-logical method, generalization method, and historical-legal method. As a conclusion of the conducted research, it can be summarized that the legislation of Ukraine is aligned with the position of most European states regarding the establishment of criminal liability for crimes against the electoral system of Ukraine within the limits of a separate norm of the Criminal Code of Ukraine. At the same time, discrepancies were found between Ukrainian and European legislation regarding the nature of the leading measures of criminal law response to the investigated crimes. A general definition of bribery in a criminal offense is given. Problematic issues of regulation prevention and detection of crimes against electoral rights are analyzed.
Kolodin D. The Influence of European Standards of Democratic Elections on the Criminal-Legal Protection of The Electoral System of Ukraine / D. Kolodin, I. Chuhunikov, A. Kolodina // Journal of Law and Political Sciences. – Denmark : Faculty of Law Aalborg Academy of Sciences, 2024. – 40(1). – P. 502-519. Режим доступу: https://hdl.handle.net/11300/32302
Keywords: bribery; election; electoral system; criminal offence; voter; provocation of bribery; crime; proof